INSURGENCY OF THE ETHNIC ARMED ORGANIZATIONS’ ROLE IN MYANMAR’S 2021 COUP: A TOTAL PEOPLE’S WAR ANALYSIS - Firdaus, Mei Rinta Sukma; Hendra, Afrizal; Hadianto, Muhammad; Timur, Fauzia Gustarina Cempaka (Jurnal Pertahanan dan Bela Negara, 2024)
This article attempts to uncover events in Myanmar during the 2021 coup and its relationship with the country's various Ethnic Armed Organizations (EAOs). The Tatmadaw initiated the 2021 coup because the civilian government's landslide victory was based on deceit and fraud. The aim was to ascertain whether the Ethnic Armed Organizations' (EAOs) inability to overturn the military coup is linked to their shortcomings in implementing the total people's war (TPW) strategy. To that end, this qualitative article utilized a historiography-analytical-based approach in its analysis. The analysis was grounded in a methodology that incorporated a framework encompassing Kiras' four concepts of a successful insurgency and Nasution's perspective on nationalism. The two methodological tools, therefore, consist of the concepts "space," "time," "support," and also "legitimacy." The EAOs' myriad backgrounds and resources make their implementation of the mentioned concept vary. The article concludes by saying that further research is needed to clarify and make other generalizations on the research question.